Investigation of the Interaction Between N-benzyl Piperidones and Bovine Serum Albumin by Spectroscopic Approaches - Yu, Xianyong; Yao, Qing; Li, Wei; Liao, Xuecheng; Yang, Ying; Liu, Heting; Li, Xiaofang; Yi, Pinggui (Journal of solution chemistry, 2012)
Fluorescence and ultraviolet spectroscopies were applied to investigate the interaction between five N -benzyl piperidones (NBP) and bovine serum albumin (BSA) under imitated physiological conditions. The experimental results show that these NBPs have a static fluorescence quenching effect on the endogenous fluorescence of BSA at the temperatures 302 and 310 K. According to the fluorescence quenching theory, the Stern–Volmer quenching constant ( K SV ), the binding constant ( K a ), and the number of binding sites ( n ) were obtained. Also, the effect of substituents on the binding capacity between NBP and BSA is in the order: C 6 H 5 < 4-CH 3 OC 6 H 4 < 4-CH 3 C 6 H 4 < 2,4-Cl 2 C 6 H 3 < 4-ClC 6 H 4 . The corresponding thermodynamic parameters (Δ G , Δ H , and Δ S ) were obtained at two different temperatures and indicate that hydrogen bonding and van der Waals forces play main roles in stabilizing the BSA–NBP complex. The binding distance between the tryptophan residue in BSA and NBP was found to be much <7 nm based on the Förster theory of non-radiation energy transfer. The effect of NBP on the conformation of BSA was analyzed as well by synchronous fluorescence spectroscopy.